Pengaruh Lingkungan Kerja, Disiplin Kerja dan Motivasi Kerja Melalui Kompetensi Guru Sebagai Variabel Mediasi Terhadap Kepuasan Kerja Guru pada SMP Pesantren Modern Terpadu Prof. Dr. Hamka II Padang - M, Agussalim; Malik’aiman, Agung; Yanti, Novi (Dinasti Review, 2023)
This study aims to examine and analyze the influence of work environment on competence, work discipline on competence, work motivation on teacher competence, work environment on job satisfaction, work discipline on job satisfaction, work motivation on teacher job satisfaction, work environment through competence as a mediating variable on job satisfaction, work discipline through teacher competence as a mediating variable on teacher job satisfaction, work motivation through competence as a mediating variable on job satisfaction. The population is 60 people and the sample is 60 people. The data analysis method is multiple linear regression analysis. The results of this study are: work environment has a positive but not significant effect on job satisfaction, work discipline has a positive and significant effect on job satisfaction, work motivation has a positive and significant effect on job satisfaction, work environment through teacher competence as a mediating variable has a positive and significant effect on competence job satisfaction, work discipline through teacher competence as a mediating variable has a positive and insignificant effect on job satisfaction, work motivation through teacher competence as a mediating variable has a negative and insignificant effect on job satisfaction.